The achievement level of the V cycle students, regarding the standard of learning: writes various types of texts - Laiza Cruz, Maricela Soledad (2020)
The objective of the study was to determine the achievement level of the V cycle students, regarding the standard of learning: writes various types of texts. This research, considered as sample, 253 students from Karol Wojtyla and Antonia Moreno de Caceres public educational institutions. The research design is non-experimental and based on a cross-sectional descriptive type with a quantitative approach. In addition, the rubric was used to assess the text production in academic papers. The results were that the achievement level of the students from both institutions is in process, regarding the learning standard: write different types of texts. In other words, students have not been able to develop the competence: production of written texts, as expected.